ETHNOCONSERVATION: RELEVANT ASPECTS AND CHALLENGES IN ITS IMPLEMENTATION - A LITERATURE REVIEW - de Santos Souza, Carolline Ângela; Thaís Duarte Brasileiro, Camilla; Gabriella Mororó Marques, Alice; de Sousa Assunção, Thays; Pereira Ramos, Rodrigo; Domingues de Faria, Marcelo (Journal of Interdisciplinary Debates, 2023)
Introduction: Biodiversity conservation is a global concern. With the advancement of agricultural frontiers, the excessive use of natural resources, pollution, urban and industrial expansion, innovative approaches that seek to face these emerging challenges become necessary; In this context, seeking practices that align scientific and traditional knowledge in biodiversity conservation, the model known as ethnoconservation emerges, which aims to strengthen the relationship between society and the environment. Objective: To address concepts of ethnoconservation, explaining the challenges for its implementation. Methodology: This is a descriptive literature review, with research carried out at Scielo and 8 articles used. Literature review: The literature addresses collective methods of appropriation of natural resources in relation to the norms of reciprocal behavior linked to them. It is pointed out that these models of cooperation and mutual assistance result in the formation of an intergroup system of economic balance. Environmental conservation, in partnership with community care, generates economic returns for the community, whether in the commercialization of products in a non-predatory way, or even in their exposure through ethnotourism. Final considerations: despite the benefits proposed by ethnoconservation, there are challenges faced in its implementation, especially in Brazil, where conservation practice is often undemocratic and distant from the knowledge of traditional populations.